The role of non-coding RNA in the diagnosis and treatment of Helicobacter pylori-related gastric cancer, with a focus on inflammation and immune response - Liu, Ao-ran; Yan, Zi-wei; Jiang, Li-yue; Lv, Zhi; Li, Yan-ke; Wang, Ben-gang (Frontiers in Medicine, 2022)
Helicobacter pylori (H. pylori) is one of the globally recognized causative factors of gastric cancer (GC). Currently, no definite therapy and drugs for H. pylori-related GC have been widely acknowledged although H. pylori infection could be eradicated in early stage. Inflammation and immune response are spontaneous essential stages during H. pylori infection. H pylori may mediate immune escape by affecting inflammation and immune response, leading to gastric carcinogenesis. As an important component of transcriptome, non-coding RNAs (ncRNAs) have been proven to play crucial roles in the genesis and development of H. pylori-induced GC. This review briefly described the effects of ncRNAs on H. pylori-related GC from the perspective of inflammation and immune response, as well as their association with inflammatory reaction and immune microenvironment. We aim to explore the potential of ncRNAs as markers for the early diagnosis, prognosis and treatment of H. pylori-related GC. The ncRNAs involved in H. pylori-related GC may all hold promise as novel therapeutic targets for immunotherapy.